An analysis of the barriers of popularizing online purchasing among corporate sector managers in Sri Lanka - Gunawardana, Kennedy D. (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
The purpose of this paper is to identify existing perceived barriers to popularizing online purchasing and to find out the relationship between perceived risk and popularizing online purchasing, with a specific focus on the influence of perceived risk. Moreover, this study aims to address on attitude towards the psychological and behavioural issues to gain consumer insights by which popularization of online transactions are most influenced. This paper tests a model of perceived risks as barriers to popularizing online purchasing. A questionnaire survey was used with a sample of 48 Sri Lankan corporate sector managers. The data was analysed using descriptive statistics and hypothesis testing. The perceived risk of issues of electronic payments, supply of personal information has a negative relationship with popularization of online purchasing. Non-online shoppers perceive higher risk than online shoppers while males perceive lower risk than females.
Keywords: Online purchasing; Perceived risk; Popularization